The Business Services Sector in Central and Eastern Europe: Territorial Embeddedness, Human Capital, and Growing Complexity - Geodecki, Tomasz; Zawicki, Marcin (Journal of Public Governance, 2021)
This special issue focuses on territorial embeddedness and growth prospects for the fast-growing Business Services Sector (BSS) in Central and Eastern European (CEE) economies. In this editorial, we introduce the topic of the special issue and outline the dimensions of territorial embeddedness of the Foreign Direct Investment (FDI) in the sector in question, taking into account the risk of relocation and the linkages between investors and local contractors. With regard to development perspectives, we draw on theory and empirical research in the field of industrial upgrading. The contributions to this special issue include six selected articles that deal with the territorial embeddedness of the business services sector in CEE, the role of human capital, the increasing complexity of services provided by this sector, office location factors, labour costs in the region, as well as the prospects of integrating the neighbouring Ukrainian economy into global value chains.